Flexural And Compressive Strength Of Brick Wall Panels With Wiremesh Reinforcement - Islamia, Rozzaana; , Muhammad Ujianto, S.T., M.T; , Yenny Nurchasanah, S.T., M.T (2016)
Wall is one of the important elements of the building and serves to separate and form a space in residential buildings or storied. In the development of the world very rapidly and building construction technology advances, many new innovations are found on the walls of one of them is a precast wall panels with reinforcement.Wall panels have a high quality and provide convenience in workability and structural systems efficiently determine the construction budget, the concrete in the wall panels were replaced by bricks coated mortar to become the cheaper alternative, and required a different method, namely red brick mounted horizontally for creating a thinner wall and efficiently. The test object is created with a size of 50 cm width, 100 cm length and 10 cm height for testing compressive strength and flexural strength, the lifes of the specimen are planned up to 28 days. On specimen maintained by way of watered.Tests performed at this research is testing the compressive strength and flexural strength at 28 days. At the lifes of 28 day compressive strength values obtained without wiremesh reinforcement of 1,878 MPa and compressive strength with wiremesh reinforcement at 2.10 MPa, for flexural strength without reinforcement wiremesh obtained a value of 1.493 MPa and with wiremesh reinforcement of 3,800 MPa. In this case the visible increase in the compressive strength and flexural due wiremesh reinforcement.